Endothelial Cell Morphology Regulates Inflammatory Cells Through MicroRNA Transferred by Extracellular Vesicles - Liang, Jiaqi; Gu, Shuangying; Mao, Xiuli; Tan, Yiling; Wang, Huanli; Li, Song; Zhou, Yue (Frontiers in Bioengineering and Biotechnology, 2020)
Vascular inflammation plays an important role in the pathogenesis and the development of cardiovascular diseases such as arteriosclerosis and restenosis, and the dysfunction of endothelial cells (ECs) may result in the activation of monocytes and other inflammatory cells. ECs exhibit an elongated morphology in the straight part of arteries but a cobblestone shape near the pro-atherogenic region such as branch bifurcation. Although the effects of hemodynamic forces on ECs have been widely studied, it is not clear whether the EC morphology affects its own function and thus the inflammatory response of monocytes. Here we showed that elongated ECs cultured on poly-(dimethyl siloxane) membrane surface with microgrooves significantly suppressed the activation of the monocytes in co-culture, in comparison to ECs with a cobblestone shape. The transfer of EC-conditioned medium to monocytes had the same effect, suggesting that soluble factors were involved in EC–monocyte communication. Further investigation demonstrated that elongated ECs upregulated the expression of anti-inflammatory microRNAs, especially miR-10a. Moreover, miR-10a was found in the extracellular vesicles (EVs) released by ECs and transferred to monocytes, and the inhibition of EV secretion from ECs repressed the upregulation of miR-10a. Consistently, the inhibition of miR-10a expression in ECs reduced their anti-inflammatory effect on monocytes. These results reveal that the EC morphology can regulate inflammatory response through EVs, which provides a basis for the design and the optimization of biomaterials for vascular tissue engineering.